Students' Journey in BS Hospitality Management Program - Majarocon, Rey II; Joy, Sonio Apreyl; Zoe, Yanoc Floren; Naparan, Genesis (Papanda Publisher, 2024)
The field of hospitality management is rapidly evolving due to global tourism growth and technological advancements. This research delves into students' journeys in hospitality management programs, examining their motivations, experiences, challenges, and career aspirations. Researchers conducted interviews with fifteen BSHM students, employing a qualitative case study. The study reveals that students are primarily motivated by the program's activities, preparation, and the dynamic nature of the hospitality industry. Academic experiences are enriched by hands-on training, internships, and industry interactions, which are crucial for bridging theoretical knowledge and practical skills. However, students need help balancing work and study, meeting high expectations for practical proficiency, and navigating a competitive job market. Career aspirations among students are diverse, ranging from hotel management and event planning to entrepreneurship and consultancy. The research underscores the necessity for academic institutions to continually adapt their programs to meet industry standards and student needs, ensuring graduates are well-prepared for the evolving demands of the hospitality sector. This study provides valuable insights for educators, policymakers, and industry stakeholders to enhance educational practices and support student success in this vibrant field.